Genetic risk factors for antiepileptic drug–induced hypersensitivity reactions in Israeli populations. (16th August 2016) - Israel, Shoshana; Maggio, Nicola; Ekstein, Dana; Zaid, Huda; Firer, Maria; Bederovsky, Yana; Noyman, Iris; Gandelman‐Marton, Revital; Blatt, Ilan; Brautbar, Chaim; Marom, Eli; Nahlieli Dil, Dorit; et al.
Summary: The human leukocyte antigen (HLA) alleles B*15:02 and A*31:01 have been identified as predictive markers of adverse cutaneous effects of carbamazepine and phenytoin in Asian and North European populations, respectively. Our aim was to estimate the distribution of these alleles in Jewish and Arab populations in Israel. The HLA‐B*15:02 and HLA‐A*31:01 carrier rate was estimated based on data from the Hadassah Bone Marrow Registry. Data on Stevens‐Johnson syndrome (SJS)– and toxic epidermal necrolysis (TEN)–related hospitalizations were obtained from the Israeli Ministry of Health (MOH) registries and from four Israeli medical centers. Of 83, 705 Jewish and Arab‐Muslim donors, 81 individuals of known origin carried the HLA‐B*15:02. Among them, 66 were Jews of India‐Cochin descent. Of the Cochin Jewish donors, 12.7% were B*15:02 carriers. HLA‐A*31:01 carrier incidence among Arab and Jewish Israeli populations (3.5% and 2.2%, respectively) was within the range reported in other countries. We did not identify SJS‐ or TEN‐related hospitalizations of Jews of Indian descent. Yet, this population should be considered at greater risk for antiepileptic drug–induced SJS and TEN. Until further data on actual risk are available, such patients should be typed for HLA‐B before treatment with carbamazepine or phenytoin.